Pengaruh Fasilitas, Motivasi dan Kedisiplinan Terhadap Prestasi Belajar MIPA di SMA Negeri 3 Klaten - Hartanto, Lilik (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The objectives to be achieved in this study are to find out, (1) To find out theinfluence of learning facilities at home on the learning achievement, learning motivation, learning discipline of Mathematics and Natural Sciences students of class XI MIPA of SMA Negeri 3 Klaten, Klaten Regency. The results showed that learning facilities at home had a positive and significant effect on the learning achievement, so that hypothesis 1 was accepted. The effective contribution of variable learning facilities at home to the learning achievement of Mathematics and Natural Sciences was 15.1% and the relative contribution was 23,%. The effective contribution of MIPA learning motivation to the MIPA learning achievement of students of Class XI MIPA in SMA Negeri 3 Klaten was 15.3% and the relative contribution was 23.7%. The effective contribution of learning discipline to the learning achievement of Mathematics and Natural Sciences students of class XI MIPA in SMA Negeri 3 Klaten was 34.2% and the relative contribution was 52.9%. MIPA learning motivation and joint learning discipline toward MIPA learning achievement 64.6% and the remaining 35.4% is influenced by other variables that are not included in this study.